Health Promoting Behaviors, Health Needs and Associated Factors among Older Adults in Jordan: A Cross-Sectional Study - Mohammad Rababa; Nahla Al Ali; Ayat Alshaman (Shiraz University of Medical Sciences, 2021)
Background: Several factors affect older adults' engagement in HPBs. This study aimed to examineHPBs, health needs, and associated factors among older adults in Jordan.Methods: A cross-sectional study was conducted on 220 older adults at one governmental and oneuniversity hospital, which were selected using convenience sampling for geographical closeness to theresearchers. All older adults with no cognitive or communication problems who attended the outpatientclinics of the two hospitals from December 2018 to April 2019 were included in the study. This timeperiod was chosen based on the convenience of the participants and researchers. Data were collected byAn Arabic version of the Health-Promoting Lifestyle Profile (HPLP) and a demographic questionnaire.The Statistical Package for Social Science (SPSS) 25.0 software was used for the descriptive andinferential analysis of the study data. The level of significance was set at p <0.05.Results: The mean score of the total HPLP was 125.33±19.09. The marital status and educational levelof the participants were associated with the total HPLP (p <0.001) in all its dimensions, except for thedimension of interpersonal relations. Participants with chronic diseases had lower scores than thosewithout diseases for the total HPLP (p <0.001) in all the six dimensions. Family income was positivelycorrelated with the dimensions of nutrition (P=0.007) and exercise (P=0.002).Conclusion: Despite the good overall mean score of older adults for total HPLP and some of itssubscales, their levels of exercise and physical activity need to be promoted. The scores of older adultswere related to various demographic and clinical factors.